1983
DOI: 10.1021/jo00159a031
|View full text |Cite
|
Sign up to set email alerts
|

Sunlamp-irradiated phase-transfer catalysis. 2. Cobalt carbonyl catalyzed carbonylation of benzyltriethylammonium or allyltriethylammonium halides under 1 atm carbon monoxide

Abstract: Benzyl‐ und Allyl‐triethylammonium‐Salze (I) liefern bei Belichtung (350 11m) und in Gegenwart von Dicobaltoctacarbonyl und Alkali die Carbonsäuren (II) in z.Tl. recht hohen Ausbeuten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…However, the stoichiometric cobalt carbonyl and methyl iodide were indispensable. Subsequently, an efficient catalytic carbonylation of benzyltriethylammonium halides was developed by Caubère and co-workers (Scheme , b) . Under photostimulation with a sun lamp, acid could be generated in high yields using 5 mol % Co 2 (CO) 8 as the catalyst.…”
Section: Caronylation Based On C–n Bond Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the stoichiometric cobalt carbonyl and methyl iodide were indispensable. Subsequently, an efficient catalytic carbonylation of benzyltriethylammonium halides was developed by Caubère and co-workers (Scheme , b) . Under photostimulation with a sun lamp, acid could be generated in high yields using 5 mol % Co 2 (CO) 8 as the catalyst.…”
Section: Caronylation Based On C–n Bond Activationmentioning
confidence: 99%
“…Subsequently, an efficient catalytic carbonylation of benzyltriethylammonium halides was developed by Caubere and coworkers (Scheme 29, b). 109 Under photostimulation with a sun lamp, acid could be generated in high yields using 5 mol % Co 2 (CO) 8 as the catalyst. Allyltriethylammonium halides were suitable substrates as well and gave the corresponding acid in good yield.…”
Section: N-center-directed Caronylation Through Single-electron Pathwaysmentioning
confidence: 99%
“…PhCH 2 NEt 3 + , m -MeC 6 H 4 CH 2 NEt 3 + , and β-naphthylmethyltriethylammonium halides afforded the acids in high yields by carbonylation with acetyl-cobalt tetracarbonyl generated from MeI and Co(CO) 4 - under PTC conditions . The Co-catalyzed carbonylation of PhCH 2 NEt 3 + X - can also be achieved by Co 2 (CO) 8 under a slow stream of CO in aqueous NaOH, even without organic solvent, provided that the reaction medium is irradiated . The reactions succeeded, affording 75−85% yield of the corresponding acids …”
Section: Carbonylation Reactionsmentioning
confidence: 99%
“…In a cautionary note concerning the use of phase-transfer catalysts (e.g., quaternary ammonium salts) in TM-catalyzed reactions, Alper and co-workers showed that benzylammonium salts are converted into the corresponding carboxylic acids using stoichiometric amounts of Co 2 (CO) 8 , under an atmosphere of CO, in the presence of base (Scheme A), and indicated that a free radical mechanism may be operating (e.g., via benzyl radical 50 ) . Soon after this, Caubere and co-workers exploited this observation and developed a catalytic variant of this reaction using visible-light photostimulation for the generation of the proposed benzyl radical intermediate . More recently, a Pd-catalyzed carbonylation of benzylic ammonium salts, via C–N bond activation, for the synthesis of amides and esters has been reported (Scheme B) .…”
Section: C–n Bond Activation Via Quaternization Of the Nitrogenmentioning
confidence: 99%
“…53 Soon after this, Caubere and co-workers exploited this observation and developed a catalytic variant of this reaction using visible-light photostimulation for the generation of the proposed benzyl radical intermediate. 54 More recently, a Pd-catalyzed carbonylation of benzylic ammonium salts, via C−N bond activation, for the synthesis of amides and esters has been reported (Scheme 6B). 55 The method tolerates a large variety of nucleophiles, including aryl-and alkylamines, α-amino esters, and alcohols.…”
Section: Introductionmentioning
confidence: 99%